Physiotherapy management in carpal tunnel syndrome cases using conservative therapy at UNS Hospital in 2025 - Samudra, Mochamad Bagoes Nata; Wahyuni, Wahyuni; Rochmah, Yunita Nur (PT WIM Solusi Prima, 2026)
Background: Carpal Tunnel Syndrome (CTS) is a median nerve compression neuropathy within the carpal tunnel characterized by pain, paresthesia, sensory disturbances, muscle weakness, and decreased hand function. This condition is commonly found in individuals with repetitive gripping activities and may significantly affect daily functional activities and quality of life. Conservative physiotherapy management is recommended as a first-line intervention for mild to moderate CTS before surgical treatment. Objective: This case report aims to evaluate the effectiveness of conservative physiotherapy management in a patient with Carpal Tunnel Syndrome at Universitas Sebelas Maret Hospital (RS UNS) in 2025. Methods: This study employed a case report design involving a 61-year-old male patient diagnosed with CTS. Physiotherapy assessment included pain evaluation using the Visual Analog Scale (VAS), range of motion measurement using a goniometer, muscle strength assessment with Manual Muscle Testing (MMT), Tinel test, and functional ability evaluation using the Wrist Hand Disability Index (WHDI). Physiotherapy diagnosis was established based on the International Classification of Functioning, Disability, and Health (ICF) framework. Conservative physiotherapy interventions consisted of infrared therapy, Transcutaneous Electrical Nerve Stimulation (TENS), ultrasound, massage, stretching exercises, and strengthening exercises. Data were analyzed descriptively. Results: Initial assessment revealed moderate pain, limited palmar flexion range of motion, decreased wrist muscle strength, sensory disturbances, and functional disability with a WHDI score of 30%, categorized as moderate disability. Following conservative physiotherapy intervention, the patient demonstrated clinical improvements including pain reduction, increased comfort during wrist movement, and enhanced hand functional ability. Conclusion: Multimodal conservative physiotherapy management was effective in reducing pain, improving wrist function, and enhancing activity and participation in a patient with Carpal Tunnel Syndrome. This approach represents a safe and evidence-based option for the initial management of CTS.